A life cycle assessment approach for sustainable residential buildings in Malaysia / Ahmad Faiz Abd Rashid - Ahmad Faiz , Abd Rashid (2017)
The building industry has a significant impact on the environment due to massive natural resources and energy it uses throughout its life cycle. Life cycle assessment (LCA) method has been accepted internationally and has been used to quantify the environmental impact of processes and products including in the building industry. The objectives of this thesis are to evaluate and benchmark conventional residential buildings and an energy efficient building in Malaysia by using LCA. This thesis has also quantified a potential environmental impact reduction by adopting selected green building standard and finally estimate the carbon emission reduction. Three residential buildings in Malaysia with different specifications were selected as case studies namely a semi-detached government quarters (GQ), a semi-detached house by a private developer (PD), and an energy efficient house (EEH). The environmental impacts of the buildings were assessed by using SimaPro under the cradle-to-grave system boundaries over a fifty years period by using CML 2001 and Eco-indicator 99. The findings of this thesis state that the energy consumption and the building materials selection have the major influence on the environmental impact. The adoption of energy efficient building products, the installation of solar panel, and a reduction in the air-conditioning usage can lower the energy consumption of the building significantly and subsequently reduce the overall environmental impact. Based on the potential improvement, it is estimated that the selected residential building in Malaysia has the potential to reduce 6.28 Mt of CO2 or 3.36% reduction in carbon emission intensity per GDP, in line with the pledge by the Prime Minister of Malaysia for 40% reduction by the year 2020. Therefore, the LCA approach to the residential building in Malaysia is crucial due to the ability to assess the environmental impact based on the selection of materials and specification of the building for further improvement even before the building is being constructed.